2021
DOI: 10.3389/fmicb.2021.695155
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Attenuates Diquat-Induced Oxidative Stress by Regulating Gut Microbiota and Metabolome Characteristics in Piglets

Abstract: Previous studies have shown that dietary resveratrol (RES) reduces diarrhea and attenuates oxidative stress in piglets challenged with diquat. However, the effect of dietary resveratrol on the gut microbiota of these piglets, as well as the potential relationships between intestinal microflora and metabolites, remain unclear. Here, 16S ribosomal DNA sequencing and metabolome analyses were performed to investigate the effect of RES on the gut microbiota and metabolome of diquat-challenged piglets. A total of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…In addition, Clostridium_sensu_stricto_1 was reported to produce VFAs using mucus-derived sugars as an energy source and promote intestinal mucus barrier adhesion to pathogens [50]. Moreover, Fu et al [51] found the abundance of Clostridium_sensu_stricto_1 significantly increased in the resveratrol group. Through correlation analysis, Zhou et al [52] showed the elevated relative abundances of Clostridium_sensu_stricto_1 in cecum contents were negatively correlated with the level of inflammatory factors IL-12, IL-6, and IFN-γ.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Clostridium_sensu_stricto_1 was reported to produce VFAs using mucus-derived sugars as an energy source and promote intestinal mucus barrier adhesion to pathogens [50]. Moreover, Fu et al [51] found the abundance of Clostridium_sensu_stricto_1 significantly increased in the resveratrol group. Through correlation analysis, Zhou et al [52] showed the elevated relative abundances of Clostridium_sensu_stricto_1 in cecum contents were negatively correlated with the level of inflammatory factors IL-12, IL-6, and IFN-γ.…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al reported that L-tryptophan supplementation improved the intestinal mucosal barrier of weaned pigs by upregulating ZO-1, ZO-3, and claudin-1, which were linked to the increased population of tryptophan-fermenting commensal bacteria Clostridium and Lactobacillus [150]. Indole and its derivatives also attenuate oxidative stress in diquat-treated pigs, as reported by Fu et al [96]. On the other hand, skatole, like indole, is also a product of microbial fermentation of tryptophan and is associated with the occurrence of undesirable odor and meat taste called 'boar-taint' in barrows [97,98].…”
Section: Indolic and Phenolic Metabolitesmentioning
confidence: 75%
“…Faecalibacterium , Escherichia-Shigella , Subdoligranulum , and Prevotella increased significantly in the AR7 group. Fu et al (2021) reported that the rise in Ruminococcaceae UCG-005 was correlated with intestinal inflammation and injury in piglets. Muribaculaceae was capable of degrading carbohydrates ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%